Profile of Patients Attending Psychiatry OPD During First Pre and Post Lock Down Period at A Tertiary Care Center of Western Nepal - Sharma, Bhaskkar; Acharya, Bishnu (Journal of College of Medical Sciences-Nepal, 2021)
Background The Government of Nepal issued a nationwide lockdown from 24th March to 21st July 2020. The study has presented the sociodemographic and clinical profile of patients during pre and post lockdown period of patients attending the psychiatry OPD of Lumbini Medical College and Teaching Hospital, Palpa, Nepal. Methods It is a retrospective study. Comparison of sociodemographic and clinical profile of the patients during the pre and post lockdown was made by applying Pearson chi-square test and analysis was done by SPSS 27.0. Results The number of patients in pre lockdown period outweighed the post lock down period. The females’ outnumbered males. Unemployment was more in post lockdown period. There were no statistically differences between the psychiatric disorders between pre and post lock down period. Conclusions The study has shown the impact of lockdown on the profile of patients.